Microcalorimetrical Study of the Effect of Selenium and Cadmium on the Growth Metabolism of Escherichia coli - Ding, L.; Li, X.; Liu, P.; Zhao, X.H. (Asian Journal of Chemistry, 2011)
A microcalorimetric technique was used to evaluate the influence of Se (selenium morpholine) and Cd2+ [Cd(NO3)2] on Escherichia coli growth. By means of 3114/3236 TAM Air isothermal calorimeter, ampoule method at 37 ºC, the thermogenic curves of E. coli growth were obtained under different conditions. In order to analyze the results, the maximum power Pm and the growth rate constants k were determined, which showed that values of Pm and k were linked to the concentration of Se and Cd2+. The results showed that a low concentration of Se (1-10 μg/mL) promoted the growth of E. coli and a high concentration of Se (> 10 μg/mL) inhibited the growth, but the Cd2+ is always inhibiting the growth of E. coli. However, there was an antagonistic or positive synergistic effect of Se and Cd2+ on E. coli when Se was 1-4 μg/mL and Cd2+ was 1-3 μg/mL. There was a negative synergistic effect of Se and Cd2+ on E. coli when Se was higher than 4 μg/mL and Cd2+ was higher than 3 μg/mL. The effect of Se and Cd2+ on E. coli was related to the formation of the Se-Cd complex compounds under different conditions chosen.